Sosialisasi sistem ijon dalam prespektif hukum islam dan kemanfaatan ekonomi dalam masyarakat: Case of Rejotangan Village, Tulungagung District - Zaki Bahrun Ni’am; Alindra Yanuardi (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
The purpose of this research is to determine the implementation of the bond agreement in the indigenous communities of Rejotangan Village, Tulungagung District, as well as the difference between the sale and purchase agreements of commodities that will exist with the indent system. Normative empirical research is used in this study. The benefit of this research is that it will offer input to the village government in order to oversee the parties that wish to tarnish the image of the customs agreement with various fraudulent firms. According to the findings of this study, the existence of the ijon agreement is motivated by an agreement between the owner of the garden and the buyer, which is based on the customs of the indigenous people involved in it and is expected to help each other in accordance with the principle of communal custom law in Islam. The bond agreement mechanism is not in writing since Rejotangan Village, Tulungagung District, still follows Customary Law.